PENGARUH AKOMODASI, FASILITAS, TRANSPORTASI, MAKANAN DAN MINUMAN HALAL TERHADAP MINAT BERWISATA HALAL BAHARI DI JAKARTA - Adinda Naziha Azzahra (2023)
Halal tourism is very important because it is one of the main pillars of the country's foreign exchange earnings. However, the number of tourists has decreased significantly in 2019 and there is still a lack of development of indicators for marine halal tourism. So this research analyzes what factors can influence tourist interest in marine halal tourism in Jakarta. This study uses a quantitative method with the data used, namely primary data derived from taking questionnaires from tourists who have visited marine tourism in Jakarta as many as 135 respondents. This research analysis technique uses the SmartPLS application. Data testing uses the outer and inner models. The result of the adjusted r-square value is 0.485 that accommodation, transportation, facilities as well as halal food and drinks are able to explain the dependent variable of this study which is equal to 48.5% and 51.5% is explained through other variables outside the research model. The results of the hypothesis test are that accommodation has a significant effect on interest, facilities do not have a significant effect on interest, transportation does not have a significant effect on interest, halal food and drinks have a significant effect on interest. It is hoped that with this research, the management of marine halal tourism in Jakarta can develop quality and continue to maintain